An alternative hypothesis for explaining anomalies in the fine scale distribution patterns of Colophospermum mopane : Are shrub and tree forms genetically distinct ? - Hempson, Gareth (Department of Biological Sciences, 2017)
Abiotic and top down control hypotheses do not adequately explain the fine scale distribution patterns of shrub and tree Colophospermum mopane (Caesalpinioideae). Genetic distinctiveness between growth forms is investigated as an alternative hypothesis. Tree and shrub C. mopane from the riparian and inland savanna zones were sampled at four sites in the northern Kruger National Park. Molecular DNA sequences were obtained for four plastid and one nuclear region, and the inter simple sequence repeat (ISSR) technique used to fingerprint individuals. Very low levels of sequence divergence were observed. The ISSR technique revealed no genetic structure between plants when grouped by growth form or by habitat in an analysis of molecular variance (AMOV A). Soil profile and xylem pressure potential data also did not explain the distribution of growth forms. A principle component analysis and a discriminant analysis of five leaf and branching characters identified a significant difference in the shape of shrub and tree C. mopane leaves. It is concluded that the C. mopane growth forms are not genetically distinct and that their fine scale distributions may be due to top down controls such as large mammals and fire.